PENGARUH PEMBERIAN ES KRIM KURMA TERHADAP TEKANAN DARAH KELOMPOK DEWASA PENDERITA PRE-HIPERTENSI - Nursanti, Firda Aulia; Isdiany, Nitta; Moviana, Yenny; Saleky, Yohannes Willihelm (Jurnal Gizi dan Dietetik, 2024)
Pre-hypertension is an early sign of hypertension. Patients with pre-hypertension have twice the risk of developing hypertension. Potassium and calcium are nutrients that can help lower blood pressure, one of which is dates and milk. The purpose of this study was to determine the effect of date ice cream administration in reducing blood pressure in patients with pre-hypertension. The research design used was a quasi experimental one group pre and post test. The intervention given was date ice cream made from 50 grams of Tunisian dates honey, 75 ml of high fat milk and 25 ml of skim milk which was given to 15 samples. The results of the bivariate test showed that there was a decrease in systolic blood pressure after the intervention of date ice cream with a p value <0.05 with an average decrease in systolic blood pressure of 11.1 mmHg and in diastolic blood pressure was 4.8 mmHg. In an effort to prevent pre-hypertension and hypertension, the community can be advised to consume foods that contain potassium and high calcium, one of which is date ice cream.